Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 7481006 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Mammalia", "HasCoordinate is true" ] } The dataset includes 7481006 records from 1250 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0025063-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences